Pengaruh Implementasi Kelas Virtual dengan Google Classroom pada Materi Laju Reaksi di Kelas XI MIPA 1 SMA Negeri 2 Langowan - Rantung, Fitria; Rumampuk, Rymond J; Gumolung, Dokri (General Chemistry Journal, 2023)
The purpose of this study was to determine the magnitude of the influence of the implementation of virtual classes with Google Classroom on the reaction rate material on student learning outcomes. This research is an experimental research, with the research design that will be used is the Pre-Experimental design, with the type of OneShot Case Study. The sample in this study was class XI MIPA 1 as an experimental class, which consisted of 25 students. Data collection was carried out by giving posttests and questionnaires after the learning process ended. The research data obtained where the regression equation is Y = 79.598 + 0.1006x with a correlation coefficient rxy = 0.785478, it is known that the magnitude of the effect of implementing virtual classes using Google Classroom media on student learning outcomes is 61.69755%. Thus it can be concluded that there is an effect of implementing virtual class learning using Google Classroom media on student learning outcomes in the matter of reaction rates.